Effect of indomethacin on embryo implantation and histomorphology of uterus, ovary, kidney, and liver of rats - Amir, Maria; Yimer, Nurhusien; Hiew, Mark; Mohd Yusoff, Sabri; Hussen, Bedru; Quddus, Abdul (Elsevier, 2023)
Background This study aimed to determine the effects of Indomethacin (IMC) treatment on embryo implantation and histomorphology of uterus, ovary, and other vital organs and its effective dosage in establishing embryo implantation dysfunction model in Sprague-Dawley (SD) rats.